Prognostic relevance of quantitative and longitudinal MOG antibody testing in patients with MOGAD: a multicentre retrospective study. Issue 3 (2nd December 2022) - Gastaldi, Matteo; Foiadelli, Thomas; Greco, Giacomo; Scaranzin, Silvia; Rigoni, Eleonora; Masciocchi, Stefano; Ferrari, Sergio; Mancinelli, Chiara; Brambilla, Laura; Mancardi, Margherita; Giacomini, Thea; Ferraro, Diana; et al.
Abstract : Background: IgG antibodies against myelin oligodendrocyte glycoprotein (MOG-IgG) define a subset of associated disorders (myelin oligodendrocyte glycoprotein associated disorders (MOGAD)) that can have a relapsing course. However, information on relapse predictors is scarce. The utility of retesting MOG-IgG over time and measuring their titres is uncertain. We aimed to evaluate the clinical relevance of longitudinal MOG-IgG titre measurement to predict relapses in patients with MOGAD. Methods: In this retrospective multicentre Italian cohort study, we recruited patients with MOGAD and available longitudinal samples (at least one >3 months after disease onset) and tested them with a live cell-based assay with endpoint titration (1:160 cut-off). Samples were classified as 'attack' (within 30 days since a disease attack (n=59, 17%)) and 'remission' (≥31 days after attack (n=295, 83%)). Results: We included 102 patients with MOGAD (57% adult and 43% paediatric) with a total of 354 samples (83% from remission and 17% from attack). Median titres were higher during attacks (1:1280 vs 1:640, p=0.001). Median onset titres did not correlate with attack-related disability, age or relapses. Remission titres were higher in relapsing patients (p=0.02). When considering the first remission sample available for each patient, titres >1:2560 were predictors of relapsing course in survival (log rank, p<0.001) and multivariate analysis (p<0.001, HR: 10.9, 95% CI 3.4 to 35.2). MOG-IgG seroconversion to negative was associated with a 95% relapse incidence rate reduction (incidence rate ratio: 0.05, p<0.001). Conclusions: Persistent MOG-IgG positivity and high remission titres are associated with an increased relapse risk. Longitudinal MOG-IgG titres could be useful to stratify patients to be treated with long term immunosuppression.